TI_GERICHTE 17.2015.202 vom 25. Januar 2016 , Richiesta di indennizzo ex art. 429 CPP. Caso semplice. Patrocinio di un avvocato non necessario - TI Tribunale d'appello (2016)
Richiesta di indennizzo ex art. 429 CPP. Caso semplice. Patrocinio di un avvocato non necessario